2020
DOI: 10.3389/fpsyg.2019.02907
|View full text |Cite
|
Sign up to set email alerts
|

Body-Centered Interventions for Psychopathological Conditions: A Review

Abstract: World-wide, billions of dollars are spent each year on body-centered interventions to alleviate both physical and psychological pathologies. Given the high demand and increasing popularity of body-centered interventions, there is need for a systematic organization of empirical evidence associated with body-centered therapies. This article reviews the psychological effects of body-centered interventions on emotional well-being, including both self and other-administered (receptive) therapies. Theory behind body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 123 publications
0
14
0
1
Order By: Relevance
“…A recent review of the literature (Tarsha et al, 2020) found that body-oriented psychological therapies were effective in reducing headaches caused by a state of tension, non-cardiac (non-specific) chest pain, psychosomatically influenced asthma diseases, and irritable bowel disease as demonstrated in other studies (Loew et al, 2001;Lahmann et al, 2008aLahmann et al, ,b, 2009. The importance of the body in psychological therapies has already been highlighted for some time by Rispoli (1999Rispoli ( , 2004Rispoli ( , 2016 who already in 1999 spoke about the unity of body and mind, overcoming this dichotomy.…”
Section: Relaxation Strategies During Pandemicsmentioning
confidence: 91%
“…A recent review of the literature (Tarsha et al, 2020) found that body-oriented psychological therapies were effective in reducing headaches caused by a state of tension, non-cardiac (non-specific) chest pain, psychosomatically influenced asthma diseases, and irritable bowel disease as demonstrated in other studies (Loew et al, 2001;Lahmann et al, 2008aLahmann et al, ,b, 2009. The importance of the body in psychological therapies has already been highlighted for some time by Rispoli (1999Rispoli ( , 2004Rispoli ( , 2016 who already in 1999 spoke about the unity of body and mind, overcoming this dichotomy.…”
Section: Relaxation Strategies During Pandemicsmentioning
confidence: 91%
“…SI, according to Ida Rolf, is a form of fascial therapy as well as postural and movement re-education. It is focused on balancing body posture, its proper alignment with gravity, and restoring the body’s maximum functional capabilities [ 10 ]. The Rolf Method of Structural Integration consists of ten sessions during which the therapist changes the position of individual parts of the body concerning the vertical and gravity field to improve the ergonomics of movements and body posture, and possibly alleviate the reported ailments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although yoga is a complex approach and difficult to standardize, it is crucial to distinctly describe the intervention procedures, both conceptually and operationally, and avoid excessive heterogeneity[ 226 , 227 ] to consider them as an integrative method in treatment plans for neuropsychological disorders[ 228 ]. Furthermore, accurate selection of populations and controls is of great importance to evaluate the potential benefit of yoga on patients with neuropsychological diseases.…”
Section: Discussionmentioning
confidence: 99%